2016
DOI: 10.12659/msm.897266
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MiR-92a May Protect Endothelial Cells After Acute Myocardial Infarction in Rats: Role of KLF2/4

Abstract: BackgroundThis study was designed to investigate the effects of microRNA-92 (miR-92), Kruppel-like factor 2 (KLF2), and Kruppel-like factor 4 (KLF4) on endothelial injury after acute myocardial infarction (AMI).Material/MethodsBlood samples were collected from 50 AMI patients for detection of cardiac troponin I (cTnI), heart-type fatty acid-binding protein (H-FABP), and von Willebrand factor (vWF). The Sprague-Dawley rat models of AMI (n=30) were established by ligating their left anterior descending coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Endothelial function is significantly impaired during the progression of AMI, which could be indicated by the inhibited cell viability [22]. For the treatment of AMI, the endothelial activation has been considered as an important signal for the therapeutic efficacy [23], and the explorations of novel molecules that serve as candidate therapeutic targets were performed by investigating the changes in endothelial function [12]. miRNAs are involved in the regulation of cell proliferation, and some members of them have been determined with pivotal roles in AMI pathogenesis by modulating endothelial cell viability [12,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial function is significantly impaired during the progression of AMI, which could be indicated by the inhibited cell viability [22]. For the treatment of AMI, the endothelial activation has been considered as an important signal for the therapeutic efficacy [23], and the explorations of novel molecules that serve as candidate therapeutic targets were performed by investigating the changes in endothelial function [12]. miRNAs are involved in the regulation of cell proliferation, and some members of them have been determined with pivotal roles in AMI pathogenesis by modulating endothelial cell viability [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of AMI, the endothelial activation has been considered as an important signal for the therapeutic efficacy [23], and the explorations of novel molecules that serve as candidate therapeutic targets were performed by investigating the changes in endothelial function [12]. miRNAs are involved in the regulation of cell proliferation, and some members of them have been determined with pivotal roles in AMI pathogenesis by modulating endothelial cell viability [12,22]. For example, Huang et al reported that miR-103a expression was elevated in AMI patients and involved in the pathogenesis of AMI by regulating the endothelial function, a result manifested by the inhibiting effect of miR-103a on cell proliferation of HUVECs [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the development of ACS, impairments in the function of VECs and the inflammatory response are considered as two important events. Some studies regarding the improvement of the two events have been conducted for the treatment of ACS [25]. For instance, miR-150 has been reported to ameliorate ACS by restoring the function of VECs, such as cell proliferation and migration [26].…”
Section: Discussionmentioning
confidence: 99%